The rock processing sector: part i: cutting technology tools, a new diamond segment band saw part ii: study of cutting forces (2010)
This article presents the state of the art in cutting procedures used for ornamental stone processing: primarily diamond segment discs, diamond wires and frame saws. In all these, a reduction in cutting thickness has a direct repercussion on profitability. A new tool is presented with a cutting thickness half that of the best achieved in conventional tools: a band saw with welded diamond segments. The first prototypes are built, cutting tests are carried out and the features of the cut are studied. In the second part, existing studies on measurement of cutting force in conventional tools are reviewed and the prototype band saw machine is monitored. Cutting forces in this new process are studied, with measurement of tangential force and feed force under various working conditions.